Illuminating geographical patterns in species' range shifts - Gaël Grenouillet; Lise Comte (Global Change Biology, 2014)
Species' range shifts in response to ongoing climate change have been widely documented, but although complex spatial patterns in species' responses are expected to be common, comprehensive comparisons of species' ranges over time have undergone little investigation. Here, we outline a modeling framework based on historical and current species distribution records for disentangling different drivers (i.e. climatic vs. nonclimatic) and assessing distinct facets (i.e. colonization, extirpation, persistence, and lags) of species' range shifts. We used extensive monitoring data for stream fish assemblages throughout France to assess range shifts for 32 fish species between an initial period (1980–1992) and a contemporary one (2003–2009). Our results provide strong evidence that the responses of individual species varied considerably and exhibited complex mosaics of spatial rearrangements. By dissociating range shifts in climatically suitable and unsuitable habitats, we demonstrated that patterns in climate‐driven colonization and extirpation were less marked than those attributed to nonclimatic drivers, although this situation could rapidly shift in the near future. We also found evidence that range shifts could be related to some species' traits and that the traits involved varied depending on the facet of range shift considered. The persistence of populations in climatically unsuitable areas was greater for short‐lived species, whereas the extent of the lag behind climate change was greater for long‐lived, restricted‐range, and low‐elevation species. We further demonstrated that nonclimatic extirpations were primarily related to the size of the species' range, whereas climate‐driven extirpations were better explained by thermal tolerance. Thus, the proposed framework demonstrated its potential for markedly improving our understanding of the key processes involved in range shifting and also offers a template for informing management decisions. Conservation strategies would greatly benefit from identifying both the geographical patterns and the species' traits associated with complex modifications of species' distributions in response to global changes.